The Contribution of Internal Audit Diamond Model in Preventing Fraud and Corruption - Evangelia Pappa; Panagiotis Kyriakogkonas; John Filos; Angeliki Samara; Georgios Georgiou (Business, Management and Economics: Research Progress Vol. 6, 2024)
Internal audit is a powerful policy tool in the private and public sectors that enhances sound financial management of organizations and ensures their sustainability by preventing fraudulent actions. The success of its implementation is focused on a multitude of factors concerning the internal environment in which it operates as well as the evolving dynamic external environment. Methodologically, the paper is based on the Internal Audit Standards and provides a systematic literature review. The theoretical model, known as the ’Diamond Model’, developed four main pillars of internal audit effectiveness: inputs (budget, staffing, internal auditors’ adequacy, digital assets); outputs (audit reports, recommendations, assurance services, consulting services); processes (planning, execution, reporting, follow-up); and internal audit relationships with all stakeholders (senior management, audit committee, auditees, external auditors). Those pillars are constrained by time, quality, quantity, and cost. The research results illuminate key aspects of internal audit effectiveness in terms of sustainable governance with emphasis on ESG criteria. The research novelty is evident in the practical usage of the Diamond Model which serves as an innovative tool for sound governance improving internal processes and operations, monitoring compliance with policies, laws, and regulations, aligning the objectives of the organization with its mission, preventing fraud and corruption, and finally adding value to the organization and improve performance of its operations.